Effect of stay in a postpartum care institution on postpartum depression in women. (March 2020) - Huang, Li-Hua; Lee, Tsung-Hsien; Huang, Jing-Yang; Ng, Soo-Cheen; Lee, Maw-Sheng; Lee, Shu-Hsin
Abstract: Introduction: Pregnancy and childbirth can cause substantial psychological and social changes and may lead to mental disorders. Women who are discharged directly from the maternity hospital after delivery without social support may have postpartum psychological health issues. Rarely have studies focused on the effect of postpartum care institutions on postpartum depression in women. Methods: We conducted a longitudinal study in Taiwan from January 2017 to July 2018. The data were collected via questionnaires administered at four time points: the first trimester of pregnancy ( n = 309), the second trimester of pregnancy ( n = 269), the third trimester of pregnancy ( n = 257) and six weeks postpartum ( n = 252). Among the participants, 130 women stayed in e postpartum care institutions, while 122 did not stay in an institution. Analysis included student t test, chi-square test, and difference in differences analysis. Linear regression analysis was used to determine the independence of the related factors for postpartum depression. Results: The women who stayed at postpartum care institutions ( n = 130) had a higher education status, higher income, higher percentage of assisted reproductive technology (ART) treatment, higher cesarean section rate, and lower postpartum Edinburgh Perinatal Depression Scale (EPDS) scores (14.6% vs. 27.8%) compared with those who did not stay at postpartum care institutions. Among the women who stayed in postpartum care institutions, the average EPDS scores were 8.74 ± 0.46 and 8.15 ± 0.49 in the ART and natural pregnancy groups at baseline (3rd month), respectively, and there was no significant difference ( p = 0.59). The EPDS scores in the ART group significantly declined at the 6th month (difference = −0.67, p <0.05), 9th month (difference = −2.00, p <0.01) and postpartum (difference = −4.01, p <0.01). Multivariate linear regression analysis indicated that postpartum care institutions was the main factor ( r = 1.38, p = 0.014) correlating to postpartum depression in women. Conclusion: Providing maternal and infant care in postpartum care institutions allows the mother to rest; and the professional guidance from the medical staff can provide the necessary support and help mothers to learn. Postpartum care institutions can decrease the incidence and severity of postpartum depression.